PENERAPAN CTL BERBANTUAN LIVEWORKSHEETS DALAM MENINGKATKAN MOTIVASI BELAJAR DAN LITERASI NUMERASI PESERTA DIDIK PADA PEMBELAJARAN FISIKA - Alfin Nuryani; Setyarsih, Woro; Jauhariyah, Mukhayyarotin Niswati Rodliyatul; Satriawan, M (IPF: Inovasi Pendidikan Fisika, 2025)
The purpose of this study was to differentiate learning motivation and numeracy literacy skills of high school students in grade XI by combining guided inquiry with the CTL approach assisted by Liveworksheets with classes without Liveworksheets. The type of research conducted was quantitative research with a Control group pretest-posttest design. The conclusions of this study include the application of learning, student learning motivation, and numeracy literacy skills. This study was designed as a quasi-experiment, with a control group tested before and after. The subjects of this study were students in grades XI-6 and XI-7 at MAN 2 Gresik, with class XI-6 as the experimental class and class XI-7 as the control class, which were selected using a purposive sampling approach. The research tools used included a numeracy literacy ability test sheet and a questionnaire about student learning motivation. The data collected were examined descriptively and quantitatively. The CTL approach significantly improved students' motivation and numeracy literacy skills (α = 5%). The results of the two-tailed t-test provide the conclusion that H0 is rejected and the results of the one-tailed t-test conducted produce the conclusion that H0 is rejected. This shows how the increase in learning motivation and numeracy literacy in classes with guided inquiry with the CTL approach assisted by Liveworksheets is better than classes without Liveworksheets. Keywords: Numeracy Literacy Skills, Motivation to Learn, CTL Approach